IMPORTANT ASPECTS OF PUBLIC PROCUREMENT PROCESS MANAGEMENT AND CONTROL (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article explores the key aspects of managing and controlling the public procurement process, which plays a vital role in ensuring transparency, efficiency, and accountability in public sector spending. The study examines the legal and institutional frameworks that govern procurement, identifies common challenges in procurement execution, and emphasizes the importance of risk management, ethical standards, and digital solutions for effective oversight. Furthermore, it highlights best practices and strategic approaches to strengthen procurement systems and enhance public trust. The article also provides recommendations for improving procurement performance through capacity building and regulatory reforms.